QUALITATIVE STUDY ON EMPLOYEE COOPERATION AND ITS IMPACT ON THE WORK ENVIRONMENT AT COFFEE KOHI - Nuratika Pasaribu; Agato Arjuna Putra Gulo; Jusni Wati Zai; Siti Nur Aisyah; Bayu Teta (CV Naskah Aceh, 2025)
This study aims to describe the forms of cooperation among employees and its impact on the work environment at Coffee Kohi Medan. Using a descriptive qualitative approach, data were collected through in-depth interviews, participatory observation, and documentation involving five employees from various divisions (waiters, barista, kitchen). The findings indicate that while employee cooperation is present, it faces challenges such as ineffective cross-divisional communication, uneven task distribution, and imbalanced workloads. Nevertheless, the existing cooperation contributes to a sense of responsibility and workplace comfort. This study highlights the importance of managerial roles in building a structured workflow system, providing team training, and encouraging open communication to create a healthy and productive work environment.